Research handbook on political propaganda / edited by Gary D. Rawnsley, Yiben Ma, Kruakae Pothong. - Rawnsley, Gary D.; Ma, Yiben; Pothong, Kruakae (Edward Elgar Publishing, 2021)
This research handbook draws on a wide range of international case studies to assess the transformative impact of modern communication landscapes on political propaganda. From Brexit to Donald Trump, from presidential elections in Mexico to political rallies in India, from 'fake news' to Cambridge Analytica, contributors demonstrate the ways in which growing digital platforms have amplified the reach and influence of political propaganda.